PATTERN OF DEMAND FOR MAKING DENTURES AT DENTAL LABORATORY IN SURABAYA CITY, INDONESIA - Setyowati, Okti; Sujati, Sujati; Wahjuni, Sri (Faculty of Vocational Studies, Universitas Airlangga, 2019)
Background: Dental laboratory in Surabaya frequently make various kinds of the denture. But surely there is a case that was the most commonly accepted, to adjust to the needs of dental laboratories on the priorities of the work was done, it was necessary to give attention to the case that many common and must be taught to students Dental Technology. Purpose: To find an overview of the number the dentures received by the dental laboratory in Surabaya from 2013 until 2017. Method: The data used is secondary data from a dental laboratory in Surabaya from 2013 to 2017. Result: A request for flexible and RPDs porcelain, acrylic resin and metal in 5 years obtained tend to be stable in high demand, even ina given year a sharp increase in RPDs flexible and drastic decline on fixed porcelain denture. Instead of facing acrylics, fixed denture tends to stabilize at its lowest during the period. While the acrylic RPDs has increased significantly in the last two years, in contrast to metal frame dentures, which decreased at two years latest. Conclusion: Flexible denture significantly better than with acrylic resin conventional denture on parameters taken in this research. Fixed porcelain denture are mostly made by a dental laboratory when compared with a removable partial denture acrylic resin.